Impact of Macro-Environmental Factors on BusinessSustainability in ‎The Leather Industry of Kanpur and Unnao, Uttar Pradesh - Brijendra, Brijendra Pratap Singh; Chaturvedi, Ashish; Mishra , Manish (International Journal of Accounting and Economics Studies, 2025)
This study examines the influence of macro-environmental factors on business sustainability in ‎the leather industry, focusing on firms in Kanpur and Unnao, Uttar Pradesh, India. A ‎quantitative approach was employed, utilizing a structured questionnaire administered to 397 ‎industry participants. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the ‎study assessed the relationships between various external forces—economic conditions, ‎government policies, environmental regulations, technological advancements, socio-cultural ‎influences, and global market trends—and business sustainability. Results indicate that ‎economic conditions and government policies significantly enhance sustainability, while ‎technological advancements have a significant negative impact, suggesting implementation ‎barriers. Other factors showed no statistically significant direct effects. The research is limited to ‎two cities and a cross-sectional design, without consideration of mediating or moderating ‎variables. Findings inform policymakers and industry leaders on the importance of financial ‎access, regulatory simplification, and technology support. This study contributes to the ‎sustainability literature by integrating diverse macro-environmental factors into a unified ‎analytical model within a traditional manufacturing context‎.